2017
DOI: 10.1016/j.bbrc.2017.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the androgenic and estrogenic properties of progestins used in contraception and hormone therapy

Abstract: Progestins used in endocrine therapies bind to multiple steroid receptors and are associated with several side-effects. It is thus important to understand the relationship between steroid receptor cross-reactivity and the side-effect profile of progestins. In cell lines that express negligible levels of steroid receptors, we report for the first time the binding affinities, potencies and efficacies of selected progestins from different generations determined in parallel. We show that the progestins bind to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…Conversely, the alternative explanation may be a protective effect of progestin based contraception against T. vaginalis likely due to hypo‐oestrogenic states which may not be conducive for persistence of T. vaginalis . However, though women using DMPA have suppressed levels of oestrogen , the same is not true for NET‐EN or implant users . Thus, this hypothesis does not fully explain the consistent finding across all the three progestin contraceptive groups.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, the alternative explanation may be a protective effect of progestin based contraception against T. vaginalis likely due to hypo‐oestrogenic states which may not be conducive for persistence of T. vaginalis . However, though women using DMPA have suppressed levels of oestrogen , the same is not true for NET‐EN or implant users . Thus, this hypothesis does not fully explain the consistent finding across all the three progestin contraceptive groups.…”
Section: Discussionmentioning
confidence: 91%
“…Another large Danish study involving 1.8 million women, followed on average for about 10.9 years, demonstrated that oral contraceptives containing synthetic progestins increased breast cancer risk (30); this is dependent on the type of progestin and duration of use. This study has major implications for the role of progestins in breast cancer and may, in fact, be in part due to the androgenic effects of synthetic progestins that are widely reported (31,32). However, a recent meta-analysis of worldwide epidemiological evidence supports the finding of increased breast cancer risk for women taking any form of progestin-containing HRT (33).…”
Section: Pr Ligandsmentioning
confidence: 76%
“…Notably, these cells are devoid of the PR and AR (Su et al, 2012b). The GR, however, is present in C6 cells and MPA binds to the GR with a high affinity, acting as a partial to a full agonist for the GR (Koubovec et al, 2004(Koubovec et al, , 2005Su et al, 2012a,b;Louw-du Toit et al, 2014). We tested the hypothesis that MPA's effects on enzymatic activity and production of MMP-9 are mediated by the GR (Figure 4).…”
Section: Medroxyprogesterone Acetate's Effects Are Mediated Through Tmentioning
confidence: 99%